2017
DOI: 10.1038/ncomms16100
|View full text |Cite
|
Sign up to set email alerts
|

Thermally stable single atom Pt/m-Al2O3 for selective hydrogenation and CO oxidation

Abstract: Single-atom metal catalysts offer a promising way to utilize precious noble metal elements more effectively, provided that they are catalytically active and sufficiently stable. Herein, we report a synthetic strategy for Pt single-atom catalysts with outstanding stability in several reactions under demanding conditions. The Pt atoms are firmly anchored in the internal surface of mesoporous Al2O3, likely stabilized by coordinatively unsaturated pentahedral Al3+ centres. The catalyst keeps its structural integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
510
4
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 632 publications
(561 citation statements)
references
References 54 publications
24
510
4
3
Order By: Relevance
“…For example, PtCu nanocage was employed as an efficient ORR electrocatalyst for primary Zn–air battery 120. Alloying Pt with other appropriate metals even coupled with supporting materials can effectively improve the utilization and reduction of Pt usages,121 but the limited reserves, high price and poor stability of noble metals still hinders their widespread implementation in Zn–air batteries 122. Consequently, tremendous efforts are devoted to exploring, designing, and preparing nonprecious metal alternatives with high performance 123.…”
Section: Primary Zn–air Batteriesmentioning
confidence: 99%
“…For example, PtCu nanocage was employed as an efficient ORR electrocatalyst for primary Zn–air battery 120. Alloying Pt with other appropriate metals even coupled with supporting materials can effectively improve the utilization and reduction of Pt usages,121 but the limited reserves, high price and poor stability of noble metals still hinders their widespread implementation in Zn–air batteries 122. Consequently, tremendous efforts are devoted to exploring, designing, and preparing nonprecious metal alternatives with high performance 123.…”
Section: Primary Zn–air Batteriesmentioning
confidence: 99%
“…Further density functional theory (DFT) calculations suggested that the Pt atoms located at the O 3 ‐terminated surface of Fe 2 O 3 (001), just like that the Fe atoms on the O 3 ‐terminated surface were replaced by isolated Pt atoms. Unlike the Pt 1 /FeO x , Zhang et al found that single Pt atoms were coordinated with four oxygen atoms on the Al 2 O 3 support ( Figure a,b), implying that the geometry environment of single atom depends on the surface structure of support. For single Pd atoms supported on microporous [Si]ZSM‐5 silicate, the Pd atoms were found to center bond with four oxygen atoms to form Pd 1 O 4 site on the internal surface microspores according to the EXAFS data .…”
Section: Unique Characteristics Of Single Metal Atom Catalystsmentioning
confidence: 99%
“…a) The k 3 ‐weighted Fourier transform of EXAFS spectra for Pt foil, H 2 PtCl 6 , PtO 2 , 0.2Pt/m‐Al 2 O 3 ‐O 2 and 0.2Pt/m‐Al 2 O 3 ‐H 2 ; b) schematic illustration of individual Pt atom located on the surface of m‐Al 2 O 3 . Reproduced with permission . Copyright 2017, Nature Publishing Group.…”
Section: Unique Characteristics Of Single Metal Atom Catalystsmentioning
confidence: 99%
“…In other way, the homogeneous common metal–organic complexes can also be used for the preparation of single‐atom metal on the support with controlled nanostructures. However, proper hard or soft templates are necessary due to the lack of ordered configurations and specific morphology . Müllen and co‐workers have fabricated a molecular metal–N x centers in porous carbon (CoN x /C) by pyrolysis of Co complexes using silica as a hard template .…”
Section: Supports and Synthetic Strategies For Sacsmentioning
confidence: 99%